Identifikasi Respon dan Kapasitas Masyarakat Kampung Wisata Rejowinangun dalam Menghadapi Pandemi Covid-19 - Putri, Shinta Permana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to identify the response and readiness of the Rejowinangun Tourism Village community in facing the Covid-19 pandemic. This research uses a combination research method. In this case, quantitative data is analyzed and identified using qualitative data support. Data was collected through an interview process with Tourism Village Managers and also a questionnaire survey of tourism business actors. The data was then analyzed using content analysis techniques and descriptive statistics. The results of the research show that in general the response of the people of Rejowinangun Tourism Village felt inadequate and unprepared to face the Covid-19 pandemic. In this case, the Covid-19 pandemic has had several impacts on them, such as decreased income, loss of work, disruption of social interactions and mental health. Even though tourism is not their main source of income, it also has an impact on their lives. They responded to the pandemic by trying to follow health protocols, monitoring developments in information and also sharing the situation with relatives. There are several community capacities in dealing with the Covid-19 pandemic by preparing savings/reserve funds and mental conditions obtained from experiences of disasters that have occurred. However, there are still several community capacities that need to be prepared to face future pandemics, namely the community's willingness to rise up, the involvement of the younger generation, and also tourism village institutions. In this case, the government also feels it is necessary to review the effectiveness of the assistance provided during the Covid-19 pandemic.